INTERNASIONALISASI KHAZANAH KESULTANAN DAN KERATON MELALUI BAHAN BACAAN BAHASA INGGRIS - Ikhsanudin, Ikhsanudin; Barella, Yusawinur (Jurnal Pendidikan Sosiologi dan Humaniora, 2022)
Information on a culture needs to be written in an international language, like English language, to make it well known internationally. Such reading materials would also have positive impact in the educational and cultural diplomacy. This article argues on the importance of the internationalization of Kalimantan Barat culture and recommends a research procedure to develop materials on Malay sultanates and palaces in Kalimantan Barat as English extensive reading sources for younger generations.   There are three foci of activity that are suggested here, namely: need analyses, designing and developing, and evaluation. The presence of such products would facilitate the local younger generations learn their cultures and English language simultaneously through extensive reading activities. The presence of confirmable materials would help reduce information bias and misunderstanding about the history and the culture. - Through extensively reading local materials that are written in English, it is expexted that the younger generations would be able to communicate their local culture and history nationally and internationally.